Neoadjuvant Chemotherapy in Muscle-Invasive Bladder Cancer - Syvänen K; Järveläinen H; Taimen P; Laato M; Boström PJ (My University, 2022)
Neoadjuvant chemotherapy (NAC) in muscle-invasive bladder cancer was introduced several years ago. Despite the evidence supporting its use in clinical practice, only a minority of patients who undergo radical cystectomy receive preoperative chemotherapy. In addition, recommendations and methods to detect patients who would benefit the most from NAC are still unclear. The European Association of Urology (EAU) guidelines panel on muscle-invasive and metastatic bladder cancer recommends the use of cisplatin-based NAC for T2-T4a, cN0 M0 bladder cancer if the patient has a performance status ≥2
and if the renal function is not impaired, but the American Urological Association, for example, does not have any guideline recommendations on this topic at all. In this review we describe the current literature supporting NAC in association with radical cystectomy in muscle-invasive urothelial carcinoma of the bladder. Evidence acquisition was made searching the Medline database for original articles published before 1st February 2014, with search terms: “neoadjuvant chemotherapy”, “radical cystectomy”, and “invasive bladder cancer”.